Tindak Tutur Guru dalam Pembelajaran Bahasa Indonesia di SMAN 4 Pasuruan - Siti Rokhimah; Mardiningsih Mardiningsih; Ilmiyatur Rosidah (SAKOLA: Journal of Sains Cooperative Learning and Law, 2024)
This study aims to describe the form of perlocutionary speech acts used by teachers in Indonesian language learning at SMAN 4 Pasuruan. Speech acts used by teachers in learning activities have been widely analyzed by previous researchers, but have not been found specifically discussing perlocutionary speech acts. This perlocutionary speech act is difficult to identify, because it must be accompanied by the context so that it causes influence by the interlocutor. This research uses descriptive research with a qualitative approach. The subject of the research is Indonesian language teachers, while the object of research is Indonesian language learning activities. The instruments in this study consisted of primary instruments, namely the researcher himself, and secondary instruments, namely data collection tables. The data of this research is the teacher's speech when conducting learning activities in class XI. The data source was obtained from the observation at the school located at SMAN 4 Pasuruan. This data collection technique uses observation, recording, interview, documentation, and recording the results of the recording in the form of data transcripts. The data analysis technique uses stages such as data reduction, data presentation, data interpretation, conclusion drawing and verification. The result of this research is the form of perlocutionary speech acts using Leech's theory. The forms of perlocutionary speech acts found include indicators of giving the interlocutor know that, persuade, encourage, annoy, frighten, please, make the interlocutor do something, inspire, impress, divert attention, make the interlocutor think about, relieve, embarrass, attract attention, and tedious. However, no data was found on the indicators of deceiving and inspiring. The form of perlocutionary speech act that is most commonly found in this study is in the indicator of encouraging and making the interlocutor do something.